The Effect of Promotion, Price, Celebrity Endorsement, Brand Image, E-Word of Mouth, and Halal Fashion Design on Muslim Fashion Sales on The TikTok Shop Platform - Alifia Hariyadi; Siti Jamilah (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This study investigates the influence of promotion, price, celebrity endorsement, brand image, electronic word-of-mouth (e-WOM), and halal fashion design on Muslim fashion sales through TikTok Shop in Indonesia using Structural Equation Modeling with Partial Least Squares (SEM-PLS) involving 150 purposively selected respondents. Results reveal that promotion (Î² = 0.446, p = 0.006) and halal fashion design (Î² = 0.361, p = 0.003) significantly drive sales, while celebrity endorsement and e-WOM show no direct impact, challenging traditional e-commerce assumptions. Halal fashion design significantly mediates the price-sales relationship (Î² = 0.336, p = 0.002), demonstrating Muslim consumers' willingness to pay premium prices for religiously compliant designs, with the model explaining 95.4% of sales variability. These findings suggest halal fashion businesses should prioritize consistent promotional campaigns leveraging TikTok's live streaming features, invest in authentic design excellence showcasing Islamic compliance, and focus on community-driven marketing rather than expensive celebrity endorsements. This research provides the first comprehensive framework for halal fashion marketing in social commerce environments, revealing how traditional e-commerce success factors require adaptation for visual-first platforms where authenticity supersedes conventional trust mechanisms.